2023
DOI: 10.1101/2023.03.21.533662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The timing of confidence computations in human prefrontal cortex

Abstract: Knowing when confidence computations take place is critical for building mechanistic understanding of the neural and computational bases of metacognition. Yet, even though substantial amount of research has focused on revealing the neural correlates and computations underlying human confidence judgments, very little is known about the timing of confidence computations. Subjects judged the orientation of a briefly presented visual stimulus and provided a confidence rating regarding the accuracy of their decisio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…However, prior research has found that an abundance of factors can cause confidence to dissociate from accuracy. Some of these include motor preparation and execution (Fleming et al, 2015; Gajdos et al, 2019; Wokke et al, 2020), transcranial magnetic stimulation (Rahnev et al, 2012, 2016; Rounis et al, 2010; Shekhar & Rahnev, 2018; Xue et al, 2023), differences in pre-stimulus brain activity Bahdo, et al, 2012; Samaha et al, 2017), confidence history (Aguilar-Lleyda et al, 2021; Rahnev et al, 2015), attention (Rahnev et al, 2011; Wilimzig et al, 2008), arousal (Allen et al, 2016), and stimulus visibility (Rausch et al, 2018, 2020). However, in this study, we only chose to test energy-induced confidence accuracy dissociations as these manipulations can be readily applied to CNNs unlike those involving motor preparation, transcranial magnetic stimulation, attention, arousal, etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior research has found that an abundance of factors can cause confidence to dissociate from accuracy. Some of these include motor preparation and execution (Fleming et al, 2015; Gajdos et al, 2019; Wokke et al, 2020), transcranial magnetic stimulation (Rahnev et al, 2012, 2016; Rounis et al, 2010; Shekhar & Rahnev, 2018; Xue et al, 2023), differences in pre-stimulus brain activity Bahdo, et al, 2012; Samaha et al, 2017), confidence history (Aguilar-Lleyda et al, 2021; Rahnev et al, 2015), attention (Rahnev et al, 2011; Wilimzig et al, 2008), arousal (Allen et al, 2016), and stimulus visibility (Rausch et al, 2018, 2020). However, in this study, we only chose to test energy-induced confidence accuracy dissociations as these manipulations can be readily applied to CNNs unlike those involving motor preparation, transcranial magnetic stimulation, attention, arousal, etc.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the preparation of incongruent actions led to a larger involvement of early attentional resources required for response inhibition which in turn influenced confidence and post-decisional markers of confidence (see above). Interestingly, a recent study suggested that TMS pulses to the dorsolateral prefrontal cortex (dlPFC) as early as 200 ms after stimulus onset affect confidence, suggesting a broad window for confidence computations beginning before the perceptual decision has been fully made, and providing evidence against strong versions of post-decisional models of confidence where confidence is exclusively computed on signals arriving after the decision has been made (Xue et al 2023). This explanation would also account for the discrepancy between the results presented here and those obtained by stimulating premotor areas (Fleming et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This selective effect clearly demonstrates the causal involvement of frontoparietal areas in metacognitive monitoring. The causal involvement of frontoparietal regions in metacognition is further supported by studies employing transcranial magnetic stimulation (TMS) (Cai et al, 2022;Luzio et al, 2022;Martin et al, 2023;Rahnev et al, 2016;Rounis et al, 2010;Ryals et al, 2016;Ruby et al, 2018;Shekhar & Rahnev, 2018;Ye et al, 2018;Xue et al, 2023a). An early study showed that offline TMS to the dorsolateral PFC decreased metacognitive sensitivity without compromising perceptual decision accuracy (Rounis et al, 2010;Ruby et al, 2018).…”
Section: Prefrontal and Parietal Regionsmentioning
confidence: 97%
“…The concept of post-decisional confidence construction has received robust support from empirical studies (Moreira et al, 2018;Yu et al, 2015), guiding subsequent investigations of confidence construction mechanisms (Fleming & Daw, 2017;Maniscalco et al, 2021;Navajas et al, 2016). Nevertheless, other research suggests that it is unlikely that confidence is formed exclusively after a decision has been made and instead confidence is likely already being computed during decision formation (Dotan et al, 2018;Chen & Rahnev, 2023;Xue et al, 2023a).…”
Section: Sequential Sampling Frameworkmentioning
confidence: 99%